The Differences in Triage Accuracy in Low and High Category Respiratory Emergency Cases Using the Early Warning System Score (EWSS) by Nursing Students - Vita Maryah Ardiyani; Wahyu Dini Metrikayanto; Ani Sutriningsih; Putu Sintya Arlinda; Risna Yekti Mumpuni; Yati Srihayati; Rosly Junaedi; Indah Dwi Pratiwi; Wyssie Ika Sari; Hardiyanto Hardiyanto (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2025)
EWSS is a cumulative scoring system that standardizes the evaluation of the severity of acute illness based on the patient's vital signs. This study aims to compare the accuracy of determining triage in cases of respiratory emergencies in cases with low and high categories to find out the extent of understanding of triage by nursing students in these two categories of cases using the EWSS method. The research was carried out at 8 institutions providing undergraduate nursing education in the city and district of Malang. The sample for this research was 200 nursing students at undergraduate and professional levels. Of the 200 students, they were divided into 2 treatment groups, namely a student group of 100 respondents who were given respiratory emergency vignette cases in the low triage category (low risk) and a student group of 100 respondents who were given cases in the high triage category (emergency). The research results show the results of the Man Whitney test with a significance result of 0.91 so it can be concluded that there are no differences in the 2 treatment groups. Almost all respondents determined triage in the 2 triage groups correctly using the EWSS triage method. EWSS can be used independently by novice nurses in carrying out triage in various cases of respiratory emergencies